PENGARUH FRAUD TRIANGLE TERHADAP DETEKSI KECURANGAN LAPORAN KEUANGAN META ANALISIS SKRIPIS MAHASISWA - Lilianda Susilo; Tania Martina Chika; Carmel Meiden; Margaretha Elisabeth (Jurnal Proaksi, 2022)
Companies must report information on the company financial statements. The suitability of financial statements is an essential factor, and if it is not appropriate, it will raise suspicion of fraud. Fraud can be carried out by the company itself or the auditor who conducts the audit. Many types of research on this theme have been carried out with different research results. This study aims to determine whether there is an influence of several factors on the fraud triangle. The object of his research is the Fraud Triangle influencing factors with a research period of 2012-2019. The data collection technique is an observation technique, the sample selection technique used is a purposive sampling technique, and the use of meta-analysis is a research analysis technique. This study indicates that Changes, Leverage, ROA, Receivables, and Audit Opinions affect fraudulent financial statements. Keywords: Fraudulent Financial Statement, Meta Analysis